2010
DOI: 10.1371/journal.pone.0012663
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Tuberculosis in the Wild Boar (Sus scrofa): A Comparison of Methods Applicable to Hunter-Harvested Animals

Abstract: BackgroundTo obtain robust epidemiological information regarding tuberculosis (TB) in wildlife species, appropriate diagnostic methods need to be used. Wild boar (Sus scrofa) recently emerged as a major maintenance host for TB in some European countries. Nevertheless, no data is available to evaluate TB post-mortem diagnostic methods in hunter-harvested wild boar.Methodology/Principal FindingsSix different diagnostic methods for TB were evaluated in parallel in 167 hunter-harvested wild boar. Compared to bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 31 publications
(77 reference statements)
2
54
2
Order By: Relevance
“…As the financial resources needed to perform bacteriological culture on a large number of samples are scarcely available, most surveys use other methods (usually gross pathology) as screening tests and only perform bacteriological culture for lesion-positive animals, sometimes as pooled samples. This introduces a bias and it was shown that the sensitivity of gross pathology was 72,2% of that obtained from bacteriology in the wild boar (Santos et al, 2010). The same trend has been reported elsewhere for deer (Rohonczy et al, 1996;O'Brien et al, 2004).…”
Section: Characterization Of Published Articlessupporting
confidence: 61%
“…As the financial resources needed to perform bacteriological culture on a large number of samples are scarcely available, most surveys use other methods (usually gross pathology) as screening tests and only perform bacteriological culture for lesion-positive animals, sometimes as pooled samples. This introduces a bias and it was shown that the sensitivity of gross pathology was 72,2% of that obtained from bacteriology in the wild boar (Santos et al, 2010). The same trend has been reported elsewhere for deer (Rohonczy et al, 1996;O'Brien et al, 2004).…”
Section: Characterization Of Published Articlessupporting
confidence: 61%
“…Serum antibodies and TB-compatible lesions are time-and cost-effective in wild boar Santos et al 2010;Boadella et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…This means defining the agent or agents: M. bovis only, or members of the M. tuberculosis complex (MTBC), or MTBC and MAP, for instance; and also defining what data will be needed, be it the antigen by culture or PCR, specific antibodies or even characteristic lesions Santos et al 2010). It is important to choose parameters for which detection tools of known effectiveness are available (Wobeser 1994).…”
Section: Recommendations For Monitoring Diseases In Wildlifementioning
confidence: 99%
“…Meat inspection is currently the only method suitable for large-scale screening in slaughtered deer, with final confirmation by culturing [64]. However, as has been shown in wild boar, this may actually not be a very sensitive method [67].…”
Section: Certification Of Btb-free Status Of Animalsmentioning
confidence: 99%
“…Direct microscopic smear examination is a fast, inexpensive method and can provide a presumptive diagnosis, especially when clinical signs and lesions are present. Its sensitivity has been reported to be variable depending on the wildlife species and severity of infection and ranged from 55.6% in wild boar [67] to 90% in white-tailed deer [73], while in lions there was an apparent absence of acid-fast bacilli in culture positive organs [22]. On the other hand, in combination with gross pathological examination, direct microscopic smear examination was found highly sensitive (95%) in infected wild boar and recommended as a useful tool for surveys and game meat inspection schemes [67].…”
Section: Direct Assaysmentioning
confidence: 99%